Predictive power of maternal serum and amniotic fluid CRP and PAPP-A concentrations at the time of genetic amniocentesis for the preterm delivery - (:unkn) unknown (ELSEVIER IRELAND LTD, 2005)
Objective: To investigate whether maternal serum and amniotic fluid CRP and PAPP-A concentrations at the time of genetic amniocentesis are markers of preterm delivery. Study design: One hundred and forty-one pregnant women were included in this prospective Study. Amniotic fluid and maternal serum CRP and PAPP-A concentrations were determined by using commercially available kits. Receiver-operating characteristic (ROC) analysis was performed to determine the efficacy of maternal serum and amniotic fluid CRP and PAPP-A levels in predicting women with preterm delivery. Results: The prevalence of spontaneous preterm delivery before 37 weeks of gestation was 9.9%. ROC analysis revealed that amniotic fluid CRP level was the only parameter, which had a significant power in the prediction of preterm delivery. The optimum cut-off level was 0.65 mg/L. The sensitivity and specificity were 92.9% and 78.7%, respectively. Conclusion: The amniotic fluid CRP level has a high sensitivity and specificity in the prediction of preterm delivery and this may be helpful in predicting preterm delivery during genetic amniocentesis. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: preterm delivery; CRP; PAPP-A; amniotic fluid; C-REACTIVE PROTEIN; MAJOR BASIC-PROTEIN; PLACENTA; MARKER; BIRTH